Isoform 1c of sterol regulatory element binding protein is less active than isoform 1a in livers of transgenic mice and in cultured cells. - Shimano, H (1997)
We have produced transgenic mice whose livers express a dominant positive NH2-terminal fragment of sterol regulatory element binding protein-1c (SREBP-1c). Unlike full-length SREBP-1c, the NH2-terminal fragment enters the nucleus without a requirement for proteolytic release from cell membranes, and hence it is immune to downregulation by sterols. We compared SREBP-1c transgenic mice with a line of transgenic mice that produces an equal amount of the NH2-terminal fragment of SREBP-1a. SREBP-1a and -1c are alternate transcripts from a single gene that differ in the first exon, which encodes part of an acidic activation domain. The 1a protein contains a long activation domain with 12 negatively charged amino acids, whereas the 1c protein contains a short activation domain with only 6 such amino acids. As previously reported, livers of the SREBP-1a transgenic mice were massively enlarged, owing to accumulation of triglycerides and cholesterol. SREBP-1c transgenic livers were only slightly enlarged with only a moderate increase in triglycerides, but not cholesterol. The mRNAs for the LDL receptor and several cholesterol biosynthetic enzymes were elevated in SREBP-la transgenic mice, but not in 1c transgenic mice. The mRNAs for fatty acid synthase and acetyl CoA carboxylase were elevated 9- and 16-fold in la animals, but only 2- and 4-fold in 1c animals. Experiments with transfected cells confirmed that SREBP-1c is a much weaker activator of transcription than SREBP-1a when both are expressed at levels approximating those found in nontransfected cells. SREBP-1c became a strong activator only when expressed at supraphysiologic levels. We conclude that SREBP-1a is the most active form of SREBP-1 and that SREBP-1c may be produced when cells require a lower rate of transcription of genes regulating cholesterol and fatty acid metabolism.